Why do climate change scenarios return to coal?. (1st December 2017) - Ritchie, Justin; Dowlatabadi, Hadi
Abstract: The following article conducts a meta-analysis to systematically investigate why Representative Concentration Pathways (RCPs) in the Fifth IPCC Assessment are illustrated with energy system reference cases dominated by coal. These scenarios of 21st-century climate change span many decades, requiring a consideration of potential developments in future society, technology, and energy systems. To understand possibilities for energy resources in this context, the research community draws from Rogner (1997) which proposes a theory of learning-by-extracting (LBE). The LBE hypothesis conceptualizes total geologic occurrences of oil, gas, and coal with a learning model of productivity that has yet to be empirically assessed. This paper finds climate change scenarios anticipate a transition toward coal because of systematic errors in fossil production outlooks based on total geologic assessments like the LBE model. Such blind spots have distorted uncertainty ranges for long-run primary energy since the 1970s and continue to influence the levels of future climate change selected for the SSP-RCP scenario framework. Accounting for this bias indicates RCP8.5 and other 'business- as -usual scenarios' consistent with high CO2 forcing from vast future coal combustion are exceptionally unlikely. Therefore, SSP5-RCP8.5 should not be a priority for future scientific research or a benchmark for policy studies. Highlights: Meta-analysis of the fossil energy outlooks used for climate change scenarios identifies a return to coal hypothesis . These projections anticipate global energy demand will counter historical trends, requiring increased per-capita coal use. The plausibility of return to coal scenarios relies on a theory of 'time-less' idealized energy resource supply curves. This theory leads IAMs to produce multi-decade energy reference cases artificially dominated by coal. Accounting for this bias indicates RCP8.5 should not be a priority for future scientific research.